2021
DOI: 10.1097/aln.0000000000004000
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pain and Age: A Retrospective Cohort Association Study

Abstract: Background As the population ages, the number of elderly people undergoing surgery increases. Literature on the incidence and intensity of postoperative pain in the elderly is conflicting. This study examines associations between age and pain-related patient reported outcomes and perioperative pain management in a dataset of surgical patients undergoing four common surgeries: spinal surgery, hip or knee replacement, or laparoscopic cholecystectomy. Based on the authors’ clinical experience, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 43 publications
5
44
4
Order By: Relevance
“…We did not find an association between female gender and increased postoperative pain intensity, as previously shown across a variety of surgical procedures [ 20 , 23 , 24 ], but as we have seen above, other studies did not find this factor [ 19 ]. Similarly, we did not find that young age is linked to increased postoperative pain, as previously reported [ 10 , 19 , 20 , 22 ], although van Dijk et al reported in a large and heterogenous international cohort that postoperative pain decreases with increasing age, but these authors qualified this relation as small and of questionable clinical significance [ 25 ].…”
Section: Discussionsupporting
confidence: 82%
“…We did not find an association between female gender and increased postoperative pain intensity, as previously shown across a variety of surgical procedures [ 20 , 23 , 24 ], but as we have seen above, other studies did not find this factor [ 19 ]. Similarly, we did not find that young age is linked to increased postoperative pain, as previously reported [ 10 , 19 , 20 , 22 ], although van Dijk et al reported in a large and heterogenous international cohort that postoperative pain decreases with increasing age, but these authors qualified this relation as small and of questionable clinical significance [ 25 ].…”
Section: Discussionsupporting
confidence: 82%
“…This may be explained by the wide range of surgical procedures included in this study, with varying sex and age distributions per surgery type, diluting possible effects of age and sex on CPSP development as was seen in previous work. 39 This study has strengths and limitations. Strengths include the prospective population-based design, the relatively large sample size, the use of high-quality data, and adherence to the TRIPOD statement's recommendations.…”
Section: Discussionmentioning
confidence: 98%
“…It evaluated short-term outcomes of preemptive analgesia with duloxetine; however, long-term outcomes such as rates of developing chronic post-surgical pain are also important and need to be evaluated. In addition, the severity of post-surgical pain might be confounded by some preoperative patient-related factors such as age, anxiety level before surgery, or gender ( Hussain et al, 2013 ; Pereira and Pogatzki-Zahn 2015 ; Thomazeau et al, 2016 ; Zorrilla-Vaca et al, 2019 ; van Dijk et al, 2021 ). The small sample size and the simple randomization employed in the current study hindered our ability to examine how these confounders might potentially impact the study outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Pharmacology frontiersin.org such as age, anxiety level before surgery, or gender (Hussain et al, 2013;Pereira and Pogatzki-Zahn 2015;Thomazeau et al, 2016;Zorrilla-Vaca et al, 2019;van Dijk et al, 2021). The small sample size and the simple randomization employed in the current study hindered our ability to examine how these confounders might potentially impact the study outcomes.…”
Section: Figurementioning
confidence: 95%